Pergeseran Budaya Nongkrong Gen-Z Makassar dari Kafe Tradisional ke Modern dalam Komunikasi Budaya - Wijaya, Lillian Sabrina; Candraningrum, Diah Ayu (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
Hanging out has become a part of the lifestyle of Makassar's youth. Generation Z is one of the generations that embraces this lifestyle. However, hanging out is no longer merely an activity for interaction. This activity has shifted to a symbol of social identity. Traditional cafes are starting to be abandoned by Gen-Z, who are turning to modern cafes. This study investigates the factors behind this shift, focusing on new interaction patterns formed in modern cafes, as well as how identity or image is constructed by Gen-Z in modern cafes. This study uses a qualitative approach with a case study method. Data collection was carried out through interviews, observation, and documentation. The results show that the shift is driven by social media trends, the aesthetics of the place, and awareness of a place's social status. New interaction patterns that occur in modern cafes are also found, namely the